Anti-Inflammatory and Anti-Arthritic Efficacies of an Indian Traditional Herbo-Mineral Medicine “Divya Amvatari Ras” in Collagen Antibody-Induced Arthritis (CAIA) Mouse Model Through Modulation of IL-6/IL-1β/TNF-α/NFκB Signaling - Balkrishna, Acharya; Sakat, Sachin Shridhar; Joshi, Kheemraj; Paudel, Sandeep; Joshi, Deepika; Joshi, Kamal; Ranjan, Ravikant; Gupta, Abhishek; Bhattacharya, Kunal; Varshney, Anurag (Frontiers in Pharmacology, 2019)
Rheumatoid arthritis (RA) is defined as a chronic autoimmune inflammatory disorder that causes damage to limb joints and progressive injuries to secondary organs. Medical practitioners prescribe Methotrexate (MTX) as standard care medicine for treating RA. However, long-term application of MTX has shown to have adverse health-related effects. Divya Amvatari Ras (DAR), an Indian Ayurvedic herbo-mineral formulation has been described in ancient texts to provide relief from RA inflammation associated distress. Therefore, in the present study, we explored the biocompatibility, anti-inflammatory and anti-arthritic efficacy of DAR using in vivo and in vitro disease models. Using carrageenan (CA) stimulated Wistar rat model of we showed a reduction in inflammation-induced paw edema using the human equivalent dose of DAR. Anti-rheumatic efficacy of DAR was studied using collagen-antibody cocktail (C-Ab) Induced Arthritis (CAIA) mouse model. The onset of RA in the CAIA mice was determined using parameters such as the increase in arthritis score, and induction of disease associated lesions in the ankle- and knee-joints, and increase in mechanical and thermal hyperalgesia. Treatment of CAIA animals with a human equivalent dose of DAR significantly reversed the RA-associated pathogenesis. These effects were comparable with the standard of care RA drug, Methotrexate. DAR acted at multiple levels of inflammation associated with RA to reduce progressive pathogenesis. Animal serum biochemistry showed DAR capable of ameliorating RA induced increase in liver enzyme Alanine Aminotransferase (ALT) and pro-inflammatory cytokine interleukin 6 (IL-6). Using lipopolysaccharide stimulated THP-1 cells, DAR was found to inhibit the expression of IL-6, IL-1β, TNF-α and upstream inflammatory gene regulatory protein, NFκB. The study endorsed the anti-arthritic and anti-inflammatory activity of the Indian Traditional Herbo-Mineral Medicine, DAR. These results also confirm that DAR was highly biocompatible and would show minimal health-related side-effects, as compared standard of care, MTX. Taken-together, we show that the DAR could be utilized a promising alternative or complementary therapy for treating rheumatoid arthritis.